2021
DOI: 10.1167/jov.21.2.9
|View full text |Cite
|
Sign up to set email alerts
|

The human visual system and CNNs can both support robust online translation tolerance following extreme displacements

Abstract: Visual translation tolerance refers to our capacity to recognize objects over a wide range of different retinal locations. Although translation is perhaps the simplest spatial transform that the visual system needs to cope with, the extent to which the human visual system can identify objects at previously unseen locations is unclear, with some studies reporting near complete invariance over 10 degrees and other reporting zero invariance at 4 degrees of visual angle. Similarly, there is confusion regarding the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
4
19
1
Order By: Relevance
“…The distinction between trained and online invariance has been the focus of recent work on translation invariance (recognizing an object at novel retinal locations after having seen it at one location). Behavioral studies have highlighted the extent to which humans possess online translation invariance (Blything et al, 2020(Blything et al, , 2021, and it is often claimed that convolutional and pooling operations endow CNNs a similar degree of online invariance to translation (Marcus, 2018;LeCun and Bengio, 1995). However, several experiments have shown that this is not the case, and indeed, CNNs not only fail to support online invariance to translation, but also fail to support online invariance to scale, rotation, and flipping along the vertical and horizontal axis (Kauderer-Abrams, 2017;Gong et al, 2014;Blything et al, 2021;Chen et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…The distinction between trained and online invariance has been the focus of recent work on translation invariance (recognizing an object at novel retinal locations after having seen it at one location). Behavioral studies have highlighted the extent to which humans possess online translation invariance (Blything et al, 2020(Blything et al, , 2021, and it is often claimed that convolutional and pooling operations endow CNNs a similar degree of online invariance to translation (Marcus, 2018;LeCun and Bengio, 1995). However, several experiments have shown that this is not the case, and indeed, CNNs not only fail to support online invariance to translation, but also fail to support online invariance to scale, rotation, and flipping along the vertical and horizontal axis (Kauderer-Abrams, 2017;Gong et al, 2014;Blything et al, 2021;Chen et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Behavioral studies have highlighted the extent to which humans possess online translation invariance (Blything et al, 2020(Blything et al, , 2021, and it is often claimed that convolutional and pooling operations endow CNNs a similar degree of online invariance to translation (Marcus, 2018;LeCun and Bengio, 1995). However, several experiments have shown that this is not the case, and indeed, CNNs not only fail to support online invariance to translation, but also fail to support online invariance to scale, rotation, and flipping along the vertical and horizontal axis (Kauderer-Abrams, 2017;Gong et al, 2014;Blything et al, 2021;Chen et al, 2017). One approach to achieving online invariance in CNNs is through architectural modification, for example, adding a Global Average Pooling layer to the end of the convolutional block results in complete translation invariance (Blything et al, 2021).…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations